ROLE OF OWNERSHIP CONCENTRATION IN CSR DISCLOSURE ON FINANCIAL PERFORMANCE - Iskandar Itan; Junnestine (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This research was carried out to examine how corporate social responsibility (CSR) can affect a company’s financial performance with the ownership concentration as the moderating variable. The CSR variable was measured using GRI G4 index, company performance was measured using return on assets (ROA), and ownership concentration was measured using the number of shares percentage. As many as 32 non-financial companies registered on the Indonesia Stock Exchange with a time span of 2015-2019 were chosen as the research samples. Secondary data were used in the form of information that can be obtained from www.idx.com and the company's website. The data obtained were further tested concerning its descriptive statistics, coefficient of determination, goodness of fit, and path coefficient using the SPSS and Smart PLS 3.0 programs, namely testing. The final conclusion taken from the research results is that CSR does not significantly affect financial performance, while ownership concentration significantly moderates the relationship between CSR and company financial performance.